2014
DOI: 10.1002/app.40425
|View full text |Cite
|
Sign up to set email alerts
|

Novel fabrication route for porous silicon carbide ceramics through the combination of in situ polymerization and reaction bonding techniques

Abstract: For the first time, an in situ polymerization technique was applied to produce mullite-bonded porous SiC ceramics via a reaction bonding technique. In this study, SiC microsized particles and alumina nanopowders were successfully coated by polyethylene (PE), which was synthesized from the particle surface in a slurry phase reactor with a Ziegler-Natta catalyst system. The thermal studies of the resulting samples were performed with differential scanning calorimetry and thermogravimetric analysis. The morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…The advantages of inorganic sol as a dispersant are as follows: it can disperse ceramic particles by a combination of electrostatic and steric effect and also provide high bond strength to ceramic bodies due to the formation of its solid gel at low temperature . Recently a new process has developed to fabricate porous SiC ceramics with improved mechanical strength by coating SiC and calcined alumina powders with a polymer (which acts as the pore former) by means of an in situ polymerization technique . Further improvement in mechanical properties with a narrow pore size distribution was obtained by chemical coating of starting SiC powders and sintering additive by alumina sol and polymer via sol‐gel process and in situ polymerization, respectively, followed by reaction bonding technique …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages of inorganic sol as a dispersant are as follows: it can disperse ceramic particles by a combination of electrostatic and steric effect and also provide high bond strength to ceramic bodies due to the formation of its solid gel at low temperature . Recently a new process has developed to fabricate porous SiC ceramics with improved mechanical strength by coating SiC and calcined alumina powders with a polymer (which acts as the pore former) by means of an in situ polymerization technique . Further improvement in mechanical properties with a narrow pore size distribution was obtained by chemical coating of starting SiC powders and sintering additive by alumina sol and polymer via sol‐gel process and in situ polymerization, respectively, followed by reaction bonding technique …”
Section: Introductionmentioning
confidence: 99%
“…Recently a new process has developed to fabricate porous SiC ceramics with improved mechanical strength by coating SiC and calcined alumina powders with a polymer (which acts as the pore former) by means of an in situ polymerization technique . Further improvement in mechanical properties with a narrow pore size distribution was obtained by chemical coating of starting SiC powders and sintering additive by alumina sol and polymer via sol‐gel process and in situ polymerization, respectively, followed by reaction bonding technique …”
Section: Introductionmentioning
confidence: 99%
“…Macroporous SiC is fabricated via various approaches including partial sintering, replica, sacrificial fugitives (pore forming agents), direct foaming, and reaction bonding . Among these, reaction‐bonded (RB) technique is most often employed since it allows a relatively low sintering temperature and low cost For examples, macroporous mullite‐bonded SiC has been fabricated via RB sintering (oxidation of SiC and mullitization between oxidation‐derived SiO 2 and additive Al 2 O 3 with using micro‐size graphite particle as pore former) . However, these studies are concerning macroporous RB‐SiC whose pore size is typically below 10 μm; there are few reports on those with pore above 10 μm.…”
Section: Introductionmentioning
confidence: 99%
“…Transmission electron microscopy revealed that a carbon layer with a uniform thickness was formed on the surface of the Si nanoparticles with the graphene addition . Recently, several researchers have shown interest in Si hybrid nanocomposites prepared by polymerization because more homogeneously dispersed nanocomposites can be obtained by increasing the interfacial interactions between two components via the formation of hydrogen bonds or covalent bonds . Zhang et al .…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Recently, several researchers have shown interest in Si hybrid nanocomposites prepared by polymerization because more homogeneously dispersed nanocomposites can be obtained by increasing the interfacial interactions between two components via the formation of hydrogen bonds or covalent bonds. [21][22][23][24] Zhang et al presented an effective approach for the synthesis of a core-shell Si hybrid nanocomposite prepared by emulsion polymerization. 25 They have claimed that the nanocomposite with polyacrylonitrile (PAN) as a shell and Si nanoparticles as the core could be applied successfully to Si-based electrode materials.…”
Section: Introductionmentioning
confidence: 99%